Post-operative Analgesia from Preemptive to Preventive Approach: Evolution and Clinical Implications (Asian Journal of Pharmaceutics (AJP), 2025)
Pain management has shifted from a reactive approach to a proactive strategy focused on prevention. Thisstudy analyzes the development, neurophysiological foundation, and clinical uses of preemptive and preventiveanalgesia in the perioperative setting. Regardless of advancements in analgesic approaches, post-operative painis frequently insufficiently managed in numerous sufferers, with more than 80% experiencing moderate-to-severe discomfort and up to 50% developing chronic pain after specific procedures. The shift from preemptiveanalgesia (interventions before surgical incision) to preventative analgesia (interventions during the perioperativephase) signifies our improved comprehension of pain processes. This article examines pain assessment tools,technological advancements, and evidence-based methodologies for implementing efficient perioperative painmanagement procedures. Multimodal strategies integrating pharmacological treatments, regional anesthesiaprocedures, and personalized care plans demonstrated substantial enhancements in patient outcomes, such asdiminished pain severity, reduced opioid usage, and a lower occurrence of chronic postsurgical pain. Futuredirections highlight individualized analgesic regimens, the use of artificial intelligence, and ongoing research intoinnovative treatment strategies to optimize pain management and improve post-operative recovery.